2015
DOI: 10.18632/oncotarget.3625
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin inhibits angiogenesis and improves defective hematopoiesis induced by tumor-derived VEGF in tumor model through modulating VEGF-VEGFR2 signaling pathway

Abstract: Curcumin, a natural polyphenol compound from the perennial herb Curcuma longa, has been proved to be beneficial for tumor-bearing animals through inhibiting tumor neovasculature formation, but the underlying mechanisms are unclear. Here, we aim to test whether curcumin affects VEGF-VEGFR2 signaling pathway and attenuates defective hematopoiesis induced by VEGF in tumor model. We demonstrated that curcumin inhibited proliferation, migration of HUVEC under VEGF stimulation and caused HUVEC apoptosis, and blocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 50 publications
(72 reference statements)
6
40
0
2
Order By: Relevance
“…Curcumin is a polyphenolic phytochemical compound, and it has multiple anti-cancer effects. For example, curcumin promotes apoptosis in several types of cancer cells [ 7 – 10 ] and inhibits migration [ 11 , 12 ] and angiogenesis [ 13 ]. Furthermore, curcumin enhances the cell death of cancer cells by anti-cancer drugs treatment, including TRAIL [ 14 – 16 ], 5-fluorouracil and gemcitabine [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a polyphenolic phytochemical compound, and it has multiple anti-cancer effects. For example, curcumin promotes apoptosis in several types of cancer cells [ 7 – 10 ] and inhibits migration [ 11 , 12 ] and angiogenesis [ 13 ]. Furthermore, curcumin enhances the cell death of cancer cells by anti-cancer drugs treatment, including TRAIL [ 14 – 16 ], 5-fluorouracil and gemcitabine [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is one cancer chemopreventive compound; it is a polyphenolic phytochemical extracted from the rhizomes of the Curcuma longa plant. Curcumin could induce apoptosis in cancer cells [19] , [20] , [21] , [22] , [23] , [24] as well as inhibit VEGF and osteopontin-induced angiogenesis [25] , [26] . Furthermore, curcumin inhibits H 2 O 2 -induced invasion of pancreatic cancer [27] and blocks invasion of ovarian cancer spheroids into the mesothelial monolayers [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the JH-CX-DG formula may have an anti-tumor angiogenesis effect. An ELISA assay revealed that JH suppressed VEGF secretion from tumor cells and inhibited cancer angiogenesis [17]. Shen et al [18] found that DG could prevent cancer cell proliferation and cancer angiogenesis by inhibiting the PI3K/AKT/mTOR signaling pathway and downregulating the expression of HIF-1α and VEGF.…”
Section: Discussionmentioning
confidence: 99%